2005
DOI: 10.1021/ef049784i
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shear and Temperature on Wax Deposition:  Coldfinger Investigation with a Gulf of Mexico Crude Oil

Abstract: The ability to determine the severity of wax deposition is an extremely important issue for the petroleum industry, particularly in the design and development of deepwater fields. Unfortunately, wax deposition is a complex process for which the mechanism is not fully understood. Furthermore, although much progress has been made in the last few decades in better understanding this complex process, the ability to accurately account for all the factors that affect deposition does not currently exist in the wax de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 6 publications
7
79
1
2
Order By: Relevance
“…The changes of carbon number distribution in deposit can be seen in Figure 3. From Table 2, the deposition rate and wax content in deposit increase with the coolant temperature decreases from WAT to pour point (PP) when the bulk oil temperature kept constant, that is to say, the deposition rate and wax content in deposit increase with the temperature differential between the bulk oil and coolant increases, which agree with the Jennings's studies (Jennings and Weispfennig, 2005). Figure 3 shows that the low carbon number components increase while high carbon number components decrease, when the coolant temperature decreases from WAT to PP with the bulk oil temperature kept constant.…”
Section: Effect Of the Coolant Temperature To Depositsupporting
confidence: 85%
See 2 more Smart Citations
“…The changes of carbon number distribution in deposit can be seen in Figure 3. From Table 2, the deposition rate and wax content in deposit increase with the coolant temperature decreases from WAT to pour point (PP) when the bulk oil temperature kept constant, that is to say, the deposition rate and wax content in deposit increase with the temperature differential between the bulk oil and coolant increases, which agree with the Jennings's studies (Jennings and Weispfennig, 2005). Figure 3 shows that the low carbon number components increase while high carbon number components decrease, when the coolant temperature decreases from WAT to PP with the bulk oil temperature kept constant.…”
Section: Effect Of the Coolant Temperature To Depositsupporting
confidence: 85%
“…When the temperature of the oil near the pipe wall is lower than the wax appearance temperature (WAT), the wax and other substances dissolved in the oil will aggregate and deposit on the pipe wall. It is generally thought by early scholars that wax deposition mechanism can be summarized as molecular diffusion, Brownian diffusion, gravity settling, or shear dispersion, and the molecular diffusion is the predominant contribution in the wax deposition process (Paso and Fogler, 2004;Creek et al, 1999;Jennings and Weispfennig, 2005;Bidmus and Mehrotra, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil temperature and wall temperature of the reference section are consistent, so there is no wax deposition on the reference section. And the test section must ensure that there is a temperature difference between oil and the tube wall, the wall temperature of the test section is lower than the oil temperature in the test section, so that the test section will appear wax deposition (Lashkarbolooki M., 2011;Liu et al, 2012;Ramirez-Jaramillo et al, 2004;Azevedo et al, 2003;Bern et al, 1980;Tian et al, 2014;Singh et al, 1999;Jennings et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The wax content and the carbon number distribution of the wax deposit has been shown to have a significant effect on the hardness and yield strength of the deposit (Bai et al 2013) observed in the field. Jennings and Weispfennig (2005) studied the effect of shear and temperature conditions used in CF studies on the amount and nature of the deposits obtained. It was observed that decreasing the thermal gradient between the oil and CF or increasing shear increased the wax content and average carbon number of the deposit.…”
Section: Introductionmentioning
confidence: 99%